The Potential of a Sumbawa Herbal Oil-Based Oleogel as Burn Wound Dressing - Yuniar, Andi Irma; Yasid, Nurul Wahidah; Nissatuljannah, Syarifah Fatimah; Rijal, Syamsu; Makmun, Armanto (Biology, Medicine, & Natural Product Chemistry, 2023)
This study aimed to innovate the current Sumbawa oil preparation which is still in the form of liquid into an oleogel so that it is easier to apply and more practical for distribution and storage. Phytochemical analysis of Sumbawa oil showed the contents of phenols, flavonoids, and alkaloids. By adding hydroxyethyl cellulose (HEC) as a gelling agent and glycerin as a humectant, Sumbawa oil can be served in the form of an oleogel. The pH measurement of the Sumbawa oil oleogel at levels of 90%, 95%, and 100% ranged from 7.0–7.3 which is the ideal acidity level for the wound healing process. In the antimicrobial activity test with S. aureus and E. coli, the zone of inhibition ranged from 12.1–14.7 mm which is considered strong. Meanwhile, in in vitro testing of the anti-inflammatory activity using the human red blood cell membrane stabilization method, the stability level of each was obtained to be 78% for 100% Sumbawa oil, 74% for oleogel with 95% Sumbawa oil, and 73% for oleogel with 90% Sumbawa oil. The oleogel morphology observation using a scanning electron microscope showed a good gelation process at 5% and 10% HEC levels.